Cartazes concretistas: arte, design gráfico e a visualidade moderna nos anos 50 e 60 no Brasil - Berclaz, Ana Paula Soares (2011)
This research is based in the history of Visual Arts and Graphic Design in Brazil during the 20th century. A focus on posters placed in exhibitions and cultural events in the years of 1950 and 1960 is studied. Through an interdisciplinary research, the thesis discusses formal visual innovations proposed in the present Concretism, and in which form these visual innovations present themselves in Visual Culture and Graphic Design of the periods being studied.